Radical Surgical Treatment of Idiopathic Tracheal Stenosis. A Clinical Observation - A. A. Pechetov; I. I. Danilov; G. A. Vishnevskaya (Креативная хирургия и онкология, 2023)
Introduction. Idiopathic cicatricial tracheal stenosis (ICTS) comprises a rare and dangerous disease of unknown etiology. Its morphological substrate consists in the formation of circular fibrotic stenosis, usually at the level of the cricoid cartilage and the first two С-shaped rings of the trachea. The first cases of the disease were described by Brandenburg only in 1972. Progression of the disease is slow, right up to severe respiratory failure and asphyxia. Treatment methods for idiopathic cicatricial tracheal stenosis include both endoscopic and open surgical techniques. However, endoscopic treatment fails to produce the desired effect. Materials and methods. The authors of the present paper performed tracheo-laryngeal resection as a radical method for treating idiopathic tracheal stenosis in a 54-year-old patient against the background of prolonged unsuccessful endoscopic treatment. The follow-up period accounted for 45 days. Examinations in the postoperative period showed complete epithelialization of the anastomosis line without inflammation. Results and discussion. Idiopathic cicatricial tracheal stenosis is considered to be a dangerous disease without significant causes of development. However, it is claimed to be a potentially curable disease, though its treatment is a difficult task. Some authors report satisfactory results of endoscopic treatment of ICTS, but most publications on this issue consider a single tracheo-laryngeal resection with anastomosis as the most optimal method of treatment, thereby correlating with the results of the present study. Conclusion. The present observation characterizes the peculiarity and possibility of radical treatment of ICTS, since the endoscopic method of treatment produces only a temporary effect. Small number of observations and lack of a coherent pathogenetic theory necessitate further research into this problem.